Survey of Understanding of Handball Games at the Student Level of the Physical Education Study Program in Bengkulu City - Rizky, Oddie Barnanda; Andika Prabowo; Bogy Restu Ilahi; Septian Raibowo; Andes Permadi; yarmani (UNIB Press, 2025)
Study aims to determine the level of understanding of physical education students in Bengkulu City towards the game of handball. The main problem in this study is that there is no data that describes the level of understanding of physical education students in Bengkulu City regarding the game. This research used a qualitative method with a descriptive approach. The research subjects were physical education students in Bengkulu City. Data collection techniques were carried out through the distribution of questionnaires, interviews, and documentation. Data analysis was carried out through three stages, namely data reduction, data presentation, and conclusion drawing and verification. Based on the results of the analysis, it was found that 3.7% (2 respondents) of the students had an understanding in the very high category, 55.55% (30 respondents) were in the high category, 40.74% (22 respondents) were in the medium category, while there were no students in the low or very low category (0%). From these results, it can be concluded that students of physical education programs in Bengkulu City have a relatively high level of understanding of handball games